Optimization of Sample Preparation Methods on Formaldehyde Analysis in Meatball with Schryver’s Method - Febrina Amelia Saputri; Nur S.B. Rosli; Wiwiek Indriyati (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Meatball is one of Indonesian’s favorite food. However, the fraudulent traders often add carcinogen compounds, formaldehyde to ensure the meatball is not easily rotten. The purpose of this study was to find out the best sample preparation method for formaldehyde analysis in the meatball. The preparation methods were the distillation, hot immersion, and cold immersion. Formaldehyde was then analyzed by Schryver’s method. UV-Vis spectrophotometer was used for quantitative analysis. The distillation method yielded the highest recovery (100.64%) compared to hot immersion (98.11%) and cold immersion (94.17%). The best method was used to test the meatball samples that have been collected around Jatinangor, Indonesia. The results of the qualitative analysis for five samples of meatball showed that two samples containing formaldehyde with the highest concentration of formaldehyde in the sample B2 (14.72ppm) and followed by B5 (8.77ppm).Keywords :  Cold immersion, distillation, formaldehyde, hot immersion, meatball, Schryver.